2013
DOI: 10.1177/1069072713487858
|View full text |Cite
|
Sign up to set email alerts
|

Major Changes

Abstract: In a sample of 346 college students, we compared students of different academic major areas in their personality characteristics, mental abilities, and vocational interests, and we examined the congruence between vocational interests and academic major as a predictor of academic outcomes (grade point average, satisfaction, and change of major). Results were mainly consistent with predicted differences between the four academic major groups (arts/humanities, business, science, and helping/child related), and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 32 publications
0
11
1
1
Order By: Relevance
“…Findings were generally consistent with the expected relationships between the HEXACO personality traits and academic performance outcomes, where Conscientiousness was related to students' self-reported GPA, and Conscientiousness, Extraversion, Openness and (to a lesser extent) Agreeableness all demonstrated positive relationships with students' engagement in a number of intellectual, interpersonal and intrapersonal behaviours. Although Honesty-Humility was related to students' ethics and integrity, the present study did not find statistically significant relationships between Honesty-Humility, its facets and GPA, thus calling into question relations between these traits and GPA (see also Pozzebon et al, 2014;de Vries et al, 2014).…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Findings were generally consistent with the expected relationships between the HEXACO personality traits and academic performance outcomes, where Conscientiousness was related to students' self-reported GPA, and Conscientiousness, Extraversion, Openness and (to a lesser extent) Agreeableness all demonstrated positive relationships with students' engagement in a number of intellectual, interpersonal and intrapersonal behaviours. Although Honesty-Humility was related to students' ethics and integrity, the present study did not find statistically significant relationships between Honesty-Humility, its facets and GPA, thus calling into question relations between these traits and GPA (see also Pozzebon et al, 2014;de Vries et al, 2014).…”
Section: Discussioncontrasting
confidence: 89%
“…Furthermore, both Honesty-Humility and Conscientiousness demonstrated relatively strong negative correlations with counterproductive academic behaviours (r = À.40 and À.42, respectively). More recently, however, a study by de Vries, Zettler, and Hilbig (2014) failed to replicate these findings for Honesty-Humility and GPA using both self-report and observer-report samples (see also Pozzebon, Ashton, & Visser, 2014).…”
Section: Interpersonal Behavioursmentioning
confidence: 99%
“…Research affirms that, of the five factors, C has the stronger predictive relationship with academic achievement (O'Connor & Paunonen, 2007;Poropat, 2009;Richardson, Abraham, & Bond, 2012). In university students-the target population of the current research-this relationship bears out with C the stronger predictor of grade point average (GPA) (Pozzebon, Ashton, & Visser, 2014). We expected to find a positive relationship between C and AA.…”
Section: Criterion Validitymentioning
confidence: 48%
“…Agreeableness, Conscientiousness, Extraversion, Neuroticism, and Openness (McCrae & Costa, 2008), several studies have explored possible group differences in the Big Five personality traits between students in different academic majors (De Fruyt & Mervielde, 1996;Kaufman, Pumaccahua, & Holt, 2013;Lievens, Coetsier, De Fruyt, & De Maeseneer, 2002;Pozzebon, Ashton, & Visser, 2014;Rubinstein, 2005). As a whole, these studies found significant personality group differences with some general trends: economics students scored low on Agreeableness and Neuroticism, while psychology and arts/humanities students scored high;…”
Section: The Big Five Personality Traits and Academic Majorsmentioning
confidence: 92%